Building Deeper Learning Through STEM Education for Elementary School Teachers - Anderson Leonardo Palinussa; Marleny Leasa; Efilina Kissiya; Jamaludin; John Rafafy Batlolona; Niel Makaruku (Pascasarjana Universitas Mataram, 2025)
STEM education (Science, Technology, Engineering, and Mathematics) in Indonesia, particularly in Maluku, faces the challenge of a skills gap that impacts economic growth. The goal of this training is to enhance teachers' competencies in integrating STEM and Deep Learning into the learning process. The training program is carried out by the Community Service Team from the Faculty of Teacher Training and Education at Pattimura University to improve teachers' understanding and ability to implement deep learning (DL) in STEM education. The results of the pre- and post-tests showed a significant increase in teachers' understanding and ability to adopt innovative educational approaches. The integration of STEM and DL has great potential to improve the quality of education. Teacher training and collaboration between educational institutions and the community are very important in enhancing the quality of education. Recommendations: (1) continuously improve teacher training, (2) develop curricula that support the integration of STEM and DL, and (3) enhance collaboration between universities and local schools to improve the quality of education and prepare students to face 21st-century challenges. Thus, it is expected to improve the quality of education and enhance students' ability to think critically and solve problems in the technological era.